2008
DOI: 10.1111/j.1365-2516.2008.01820.x
|View full text |Cite
|
Sign up to set email alerts
|

Ankle surgery in haemophilia with special emphasis on arthroscopic debridement

Abstract: Various conservative options are available to treat ankle problems in haemophilia, which achieve a high rate of satisfactory results in the majority of cases. They are usually employed in combination and include the use of patellar tendon bearing (PTB) orthoses and radiosynoviorthesis. The effect of the PTB orthoses is that it allows the patient to walk without weight bearing of the ankle. Radiosynoviorthesis can be performed in cases of haemophilic arthropathy of the ankle, provided there is at least a minima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 20 publications
0
36
0
1
Order By: Relevance
“…Most studies have reported decreased haemarthrosis and improved clinical outcomes postoperatively. However, the study reported by Rodriguez‐Merchan involving patients aged <20 years and another study showed that arthroscopic synovectomy only temporarily improved symptoms and was associated with postoperative neurological complications and infections …”
Section: Discussionmentioning
confidence: 96%
“…Most studies have reported decreased haemarthrosis and improved clinical outcomes postoperatively. However, the study reported by Rodriguez‐Merchan involving patients aged <20 years and another study showed that arthroscopic synovectomy only temporarily improved symptoms and was associated with postoperative neurological complications and infections …”
Section: Discussionmentioning
confidence: 96%
“…However, VWD is a known reason for haemophilic arthropathy. ankle arthrodesis, TAR) [15,29,[55][56][57][58][59][60][61][62][63]. Sood et al [8] described similarity in joint function limitations in patients with Type 3 VWD and moderate haemophilia A.…”
Section: Discussionmentioning
confidence: 99%
“…16 Treatment recommendations for patients with chronic synovitis and arthropathy should be made after careful consideration of all potential options. Surgical intervention is indicated when conservative treatment fails.…”
mentioning
confidence: 99%